RISK MANAGEMENT IN NEW PRODUCT DEVELOPMENT AT COSMETIC PRODUCTS MANUFACTURER COMPANY (PT X) - Muna, Luthfiatul
PT X is an Indonesian Cosmetic Manufacturer. The large number of business actors who are dominated by Small and Medium-sized Enterprises (SMEs) causes intense competition in the local cosmetic industry so that product innovation is necessary. The limitations faced by SMEs in developing new cosmetic products have caused many local cosmetic manufacturers prefer to use the services of PT X to develop new cosmetic products. However, during its journey, PT X still encounters many disruptions and obstacles in developing new products based on request and product specifications from client. These disruptions urge PT X to realize the need to implement risk management in new product development projects to minimize risks within the projects. The application of risk management in product development projects at PT X uses the House of Risk model (Pujawan & Geraldin, 2009). House of Risk is carried out in two stages, namely the first phase of HOR which aims to identify risks and causes of risk (risk agents) and determine critical risk agents. The first HOR phase is conducted by identifying risk events and risk agents, assessing the severity of risk events, occurrence of risk agents, and the relationship between risk events and risk agents. The second phase of HOR aims to determine the handling of risk agents in preventing the same risk from happening again. The second phase of HOR is conducted by determining the critical risk agent, designing the response for the risk agent and assessing the response of the risk agent based on the effectiveness of the risk agent's response and the degree of difficulty in implementing the risk agent's response. The number of identified risk events is 75 risk events caused by 83 risk agents. Based on the results of the assessment of risk events and risk agents, there are 35 critical risk agents. The critical risk agent response design resulted in 51 risk agent responses with 3 of them removed because they were not relevant in minimizing the occurrence of risk agents.